2010
DOI: 10.1002/pssc.200982721
|View full text |Cite
|
Sign up to set email alerts
|

Performance and stability of low temperature hydrogenated amorphous silicon thin film transistors fabricated on stainless steel substrate

Abstract: The key development issues in the flexible displays are TFT backplane technology, which requires competitive device performance and low temperature process compatible with flexible substrate. Here, we have fabricated low temperature hydrogenated amorphous silicon thin film transistor on a stainless steel substrate coated with organic barrier layer. Then, we have studied initial device performance by varying plasma gas and pressure conditions at a low power and a low temperature during amorphous silicon and sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In PECVD technique, it was found that several deposition parameters, such as gas flow rate, excitation power, pressure, substrate temperature and dilution of the source gas (silane) with other gases (argon, hydrogen, or helium) influence the structure and properties of the growth of a-Si:H thin film [2,3]. Silicon thin films deposited at low temperatures by PECVD technique have been shown to exhibit good quality and stability for solar cell and TFT applications [6][7][8][9][10]. For solar cell applications, thickness-dependent morphology of protocrystalline Si films grown at the borderline between a-Si: H and nc-Si: H phases was revealed by absolute constant photocurrent method (CPM) [8].…”
Section: Introductionmentioning
confidence: 99%
“…In PECVD technique, it was found that several deposition parameters, such as gas flow rate, excitation power, pressure, substrate temperature and dilution of the source gas (silane) with other gases (argon, hydrogen, or helium) influence the structure and properties of the growth of a-Si:H thin film [2,3]. Silicon thin films deposited at low temperatures by PECVD technique have been shown to exhibit good quality and stability for solar cell and TFT applications [6][7][8][9][10]. For solar cell applications, thickness-dependent morphology of protocrystalline Si films grown at the borderline between a-Si: H and nc-Si: H phases was revealed by absolute constant photocurrent method (CPM) [8].…”
Section: Introductionmentioning
confidence: 99%